PHIRE (Public Health Innovation and Research in Europe): methods, structures and evaluation - Barnhoorn, Floris (2013)
Public Health Innovation and Research in Europe (PHIRE), building on previous European collaborative projects, was developed to assess national uptake and impacts of European public health innovations, to describe national public health research programmes, strategies and structures and to develop participation of researchers through the organizational structures of the European Public Health Association (EUPHA). This article describes the methods used.